Bioactive flavonoids in medicinal plants: Structure, activity and biological fate - Tian-yang Wang; Qing Li; Kai-shun Bi (Elsevier, 2018)
Flavonoids, a class of polyphenol secondary metabolites, are presented broadly in plants and diets. They are believed to have various bioactive effects including anti-viral, anti-inflammatory, cardioprotective, anti-diabetic, anti-cancer, anti-aging, etc. Their basic structures consist of C6C3C6 rings with different substitution patterns to produce a series of subclass compounds, and correlations between chemical structures and bioactivities have been studied before. Given their poor bioavailability, however, information about associations between structure and biological fate is limited and urgently needed. This review therefore attempts to bring some order into relationships between structure, activity as well as pharmacokinetics of bioactive flavonoids.